2011
DOI: 10.1016/j.jacc.2010.09.082
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Event Reduction and Adverse Events Among Subjects Attaining Low-Density Lipoprotein Cholesterol <50 mg/dl With Rosuvastatin

Abstract: Among adults with LDL-C <130 mg/dl and high-sensitivity C-reactive protein ≥2 mg/l, rosuvastatin-allocated participants attaining LDL-C <50 mg/dl had a lower risk of cardiovascular events without a systematic increase in reported adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
60
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 203 publications
(68 citation statements)
references
References 40 publications
4
60
0
2
Order By: Relevance
“…Baseline features of the JUPITER population are described elsewhere. [24][25][26] Association With Baseline CK: GoDARTS and JUPITER CK levels were statistically significantly associated with the CKM Glu83Gly variant (n=4598, P value=2×10 −16 ) in the GoDARTS population. Carriers of the CKM variant CKM Glu83Gly, Creatine Kinase, and Myalgia (Glu83Gly:T/C) had mean CK of 86 (±68) compared with 126 (±82) for homozygotes of the common allele as seen in Table 2.…”
Section: Baseline Characteristics Of the Godarts Study Populationmentioning
confidence: 95%
See 1 more Smart Citation
“…Baseline features of the JUPITER population are described elsewhere. [24][25][26] Association With Baseline CK: GoDARTS and JUPITER CK levels were statistically significantly associated with the CKM Glu83Gly variant (n=4598, P value=2×10 −16 ) in the GoDARTS population. Carriers of the CKM variant CKM Glu83Gly, Creatine Kinase, and Myalgia (Glu83Gly:T/C) had mean CK of 86 (±68) compared with 126 (±82) for homozygotes of the common allele as seen in Table 2.…”
Section: Baseline Characteristics Of the Godarts Study Populationmentioning
confidence: 95%
“…Only treatment-emergent adverse events were reported. 26 Myalgia was observed in 837 trial participants and was reported by Hsia et al 26 to be independent of their assigned therapy.…”
Section: Myalgia In Jupitermentioning
confidence: 97%
“…Similarly, in the Justification for the Use of Statins in Prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER), among patients treated with rosuvastatin, attainment of LDL-C <50 mg/dL compared with LDL-C >50 mg/ dL was associated with a lower risk of cardiovascular events without significant differences in safety. 7 Ezetimibe, a nonstatin drug that decreases intestinal absorption of cholesterol, also lowers LDL-C. In a recent randomized trial of patients with acute coronary syndromes, a combination of ezetimibe and simvastatin resulted in low LDL-C levels (≈50 mg/dL) and reduced risk of subsequent cardiovascular events when compared with simvastatin monotherapy.…”
Section: Article See P 731mentioning
confidence: 99%
“…4 Likewise, the Justification for the Use of statins in Prevention: an Intervention Trial Evaluating Rosuvastatin (JUPITER) trial demonstrated a lower risk of ischemic events in patients with LDL-C <50 mg/dL vs. patients with LDL-C >50 mg/dL without any adverse effects. 5 Lately, the Improved Reduction of Outcomes: Vytorin Efficacy International Trial (IMPROVE-IT TIMI 40) trial further validated the concept that achieving very low LDL-C translates to favorable cardiac outcomes. IMPROVE-IT was a double-blind, randomized, placebo-controlled trial in which 18, 144 patients with acute coronary syndrome were treated with simvastatin and ezetimibe or simvastatin alone and followed for 7 years.…”
mentioning
confidence: 99%